#TITLE_ALTERNATIVE# - ANDRE NILSON (NIM 15108066) ; pembimbing : Prof.Ir. Hasanuddin Z. Abidin, M.Sc., Ph.D. Irwan Gumila
TLS (Terrestrial Laser Scanning) has become the latest technology that produces three-dimensional models with high resolution. Initially the use of TLS is for object modeling, identification, and preservation of historical sites only. But by applying such technology that is applied to the measurement tools and by more perfect post- processing stages, accuracy of identification and filtering can be enhanced for the needs of other studies .The use of TLS has evolved into a tool of topographic mapping or modeling of natural and artificial objects. In addition, when modeling the same object at different time (epoch), the changes in the object can be recorded and counted for the purposes of research or mitigate the effects of the change on the object. This process is known as the study of deformation, which is the process of measuring and analyzing the phenomenon of change of natural objects (soil erosion, volcanic deformation, coastal erosion etc.) or artificial objects (elevation reduction and cracks of building surface caused by external force). This research discuss the use of TLS, especially the study of natural deformation based on previous studies that have been done and published in various international journals.The maximum measurement precission of TLS for monitoring landslides, volcanic activity and coastal erosion is: the registration accuracyis up to 5.5 mm and georeferencing is up to 12.5 mm.